Analysis of Alveolar Crest Reduction Post Extraction with the Use of Platelet Rich Fibrin (PRF) - Amelia, Rezky; Fauzi, Abul; Prasetiawaty, Eka (Migration Letters, 2023)
One of the treatments that can be done to treat dental and oral diseases is tooth extraction. However, this procedure can cause significant changes in the dimensions of the alveolar ridge that are unfavorable in subsequent oral rehabilitation. One of the most important things is the preservation of the remaining alveolar ridge after the tooth extraction procedure. The use of Platelet Rich Fibrin (PRF) for the regeneration of soft and hard tissue in wound healing, in the form of immune concentrate and platelets obtained from a single fibrin membrane which contains all the blood constituents useful for healing and immunity. This research is an unblinded, randomized clinical trial with a sample size of 36 patients undergoing tooth extraction. To see the effect of ridge resorption analysis, namely the reduction of the alveolar crest with PRF application. Each research sample is analyzed at each evaluation time. There was a significant difference in alveolar crest reduction in the treatment and control groups which was found in the mesial region (post-extraction days 60 and 90) and distal region (post-extraction days 30, 60 and 90) with a significance value p<0.05. There was a significant difference in the periapical x-ray image in the reduction of the post-extraction alveolar crest in the PRF application group, with better results compared to the group without PRF.